Synergistic and antagonistic interactions of oxybenzone and ocean acidification: new insight into vulnerable cellular processes in non-calcifying anthozoans - Morgan, Michael B.; Williams, Jacob; Breeze, Barrett; English, Nicholas; Higdon, Nathaniel; Onthank, Kirt; Qualley, Dominic F. (Frontiers in Physiology, 2024)
Cnidarians face threats from ocean acidification (OA) and anthropogenic pollutants such as oxybenzone (BP-3). Threats from multiple stressors is an important area to investigate because of synergistic or antagonistic interactions. Realtime quantitative PCR characterized the expression profiles of twenty-two genes of interest (GOI) in sea anemones (Exaiptasia diaphana) exposed to one of four treatments: 1) 96hr of OA conditions followed by a 4hr exposure to 20 ppb BP-3; 2) Exposure to 4hr 20ppb BP-3 without 96hr of OA; 3) Exposure to 96hr of OA alone; or 4) laboratory conditions with no exposure to BP-3 and/or OA. These 22 GOIs represent cellular processes associated with proton-dependent transport, sodium-dependent transport, metal cation binding/transport, extracellular matrix, amino acid metabolism/transport, immunity, and/or steroidogenesis. These 22 GOIs provide new insight into vulnerable cellular processes in non-calcifying anthozoans exposed to OA and BP-3. Expression profiles were categorized as synergistic, antagonistic, or additive of BP-3 in the presence of OA. Two GOIs were synergistic. Fifteen GOIs were antagonistic and the remaining five GOIs were additive in response to BP-3 in acidified seawater. A subset of these GOIs appear to be candidate biomarkers for future in situ investigations. In human health, proton-dependent monocarboxylate transporters (MCTs) are promising pharmacological targets and recognized as potential biomarkers. By comparison, these same MCTs appear to be targets of xenobiotic chemical pollutants in cnidarian physiology.In the presence of BP-3, a network of collagen synthesis genes are up-regulated and antagonistic in their expression profiles. Cytochrome b561 is a critical protein required for collagen synthesis and in silico modeling demonstrates BP-3 binds in the pocket of cytochrome b561.Understanding the underlying molecular mechanisms of "drug-like" compounds such as BP-3 may lead to a more comprehensive interpretation of transcriptional expression profiles. The collective antagonistic responses of GOIs associated with collagen synthesis strongly suggests these GOIs should be considered candidate biomarkers of effect. GOIs with synergistic and additive responses represent candidate biomarkers of exposure. Results show the effects of OA and BP-3 are interactive with respect to their impact on cnidarians. This investigation offers mechanistic data that supports the expression profiles and underpins higher order physiological responses.